2019
DOI: 10.1080/07420528.2019.1663863
|View full text |Cite
|
Sign up to set email alerts
|

The daily, weekly, and seasonal cycles of body temperature analyzed at large scale

Abstract: As a check for biases that could be introduced by the use of data from an emergency department, we repeated the study analyses after excluding all temperatures in the fever range (≥38.0°C, ≥100.4°F). The exclusion did not cause bathyphase (hollow points) or orthophase (solid points) to change significantly, though it widened their confidence intervals, especially for orthophase. Bathyphase refers to the time of the minimum value in the diurnal cycle of body temperature. Orthophase refers to the time of the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…16 We also observed that mean body temperature followed a consistent diurnal cycle across days of the week and seasons of the year in the Boston ED. 17 These results suggested that it would be useful to study how body temperature cycles relate to fever presentation. However, except for Wunderlich's research from the 1800s, 6 little evidence was available to prepare specific research hypotheses.…”
Section: Study Planningmentioning
confidence: 99%
“…16 We also observed that mean body temperature followed a consistent diurnal cycle across days of the week and seasons of the year in the Boston ED. 17 These results suggested that it would be useful to study how body temperature cycles relate to fever presentation. However, except for Wunderlich's research from the 1800s, 6 little evidence was available to prepare specific research hypotheses.…”
Section: Study Planningmentioning
confidence: 99%
“…Rectal temperature tends to be about 0.5 • C (0.9 • F) higher than an oral temperature (Bijur et al, 2017). Afternoon temperature may, on average, be 0.3 • C (0.5 • F) higher than morning temperature (Harding et al, 2019). In women, ovulation also increases temperature between 0.28 • C (0.5 • F) and 0.56 • C (1.0 • F) in the second half of the menstrual cycle (Shilaih et al, 2018).…”
Section: Elevated Body Temperature -The Cut-off Pointmentioning
confidence: 94%
“…Body licking was counted when mice showed saliva spreading 53 . Sleeping behavior was counted when mice showed behaviors such as curling up or body extension 54,55 .…”
Section: Recording Of Behaviorsmentioning
confidence: 99%